The Ratio Decidendi of the Religious Court Judge in Ponorogo in Determining Nafkah Iddah and Mut'ah from the Perspective of Fath al-Dzari'ah. - LILIA PRASASTI (Pro Justicia: Jurnal Hukum dan Sosial, 2025)
The ratio decidendi of Religious Court judges in divorce cases represents the reasoning behind a court decision and forms part of the judgment delivered at the conclusion of a case. Through fact analysis, judges apply relevant legal principles or norms and render decisions on divorce cases. This study adopts a qualitative approach with an empirical research type, based on primary and secondary data sources. Data collection was conducted by analyzing judicial verdicts, as well as interviews with judges, court clerks, and the public relations staff of the Ponorogo Religious Court. The data analysis techniques included data presentation, data reduction, and data verification. The research findings indicate factors influencing the ratio decidendi of Religious Court judges in divorce cases caused by adultery, as the basis for determining mut'ah and iddah maintenance, include the husband's goodwill, relevant laws, such as Supreme Court Regulations (Perma) and Circular Letters (SEMA), and the availability of property that can be granted. And also the ratio decidendi of Religious Court judges in determining mut'ah and ‘iddah from the perspective of fathu dzari'ah can be seen from two considerations: first, the motive or purpose of the ruling and the impacts resulting from it, and second, the consequences arising from the ruling regardless of the motive or intention of the perpetrator.